Development Of Pharmacist Counseling Application Android-Based For Hypertension Patients - Sri Haryanti; Kyky Herlyanti; Putri Maharani (Media Farmasi Indonesia, 2025)
In Indonesia the use of telepharmacy in clinical services is still not widely utilized. The counseling activities conducted by community pharmacists have not yet been optimal, and the documentation related to clinical pharmacy services is still considered very poor. This research aims to determine the usability of the Android-based pharmacist counseling application developed for hypertensive patients. The usability of the application includes the criteria of usefulness, ease of use, ease of learning, and user satisfaction. The method used in this research is Research and Development with the 4D model (define, design, develop, and disseminate). The sample in this study consists of 45 pharmacists practicing in pharmacies in Semarang City and 100 patients aged 18-40 years residing in Semarang City. The sampling technique in this study used purposive sampling. Usability testing used the USE questionnaire via Google Forms with assessment using a Likert scale. The collected data were analyzed using usability percentages. The research results show that the developed Android-based pharmacist counseling application for hypertensive patients meets usability criteria with a usefulness score of 87.66%, ease of use score of 91.40%, ease of learning score of 93.48%, and user satisfaction score of 87.92%.